Inducible reporter/driver lines for the Arabidopsis root with intrinsic reporting of activity state. (23rd January 2019) - Machin, Frank Qasim; Beckers, Malin; Tian, Xin; Fairnie, Alice; Cheng, Teri; Scheible, Wolf‐Rüdiger; Doerner, Peter
Summary: Cell‐, tissue‐ or organ‐specific inducible expression systems are powerful tools for functional analysis of changes to the pattern, level or timing of gene expression. However, plant researchers lack standardised reagents that promote reproducibility across the community. Here, we report the development and functional testing of a Gateway‐based system for quantitatively, spatially and temporally controlling inducible gene expression in Arabidopsis that overcomes several drawbacks of the legacy systems. We used this modular driver/effector system with intrinsic reporting of spatio‐temporal promoter activity to generate 18 well‐characterised homozygous transformed lines showing the expected expression patterns specific for the major cell types of the Arabidopsis root; seed and plasmid vectors are available through the Arabidopsis stock centre. The system's tight regulation was validated by assessing the effects of diphtheria toxin A chain expression. We assessed the utility of Production of Anthocyanin Pigment 1 (PAP1) as an encoded effector mediating cell‐autonomous marks. With this shared resource of characterised reference driver lines, which can be expanded with additional promoters and the use of other fluorescent proteins, we aim to contribute towards enhancing reproducibility of qualitative and quantitative analyses. Significance Statement: This work reports the generation of common reference lines that drive and report expression of the estradiol‐inducible synthetic transcription factor XVE in different cell types and tissue domains of the Arabidopsis root. The availability of such lines from the Stock Centre will promote comparability and reproducibility of results within and between laboratories.